PERBANDINGAN STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE DENGAN PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN - Sita Widia Wati; Chomsatu, Yuli; Nikmatul Fajri, Rosa (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to determine the effect of profitability, asset structure, liquidity, and sales growth on capital structure in property and real estate sub-sector companies as well as construction and building sub-sector companies as well as comparing the capital structure of the two companies. The population of this research is all of the property and real estate sub-sector companies and construction and building sub-sector companies in 2016-2018. The sampling technique is purposive sampling. Hypothesis testing techniques using multiple linear regression analysis and independent sample t-test different test. Based on the test results above shows that the asset structure and liquidity variables affect the capital structure while profitability and growth do not affect the capital structure in the property and real estate sub-sector companies. Whereas in the construction and building sub-sector companies show that sales growth variables affect the capital structure while profitability, asset structure, and liquidity do not affect the capital structure. The results of the different independent sample t-test concluded that there were differences in capital structure between the property and real estate sub-sector companies and the construction and building sub-sector companies.